Pengaruh Letak Bracing Pada Menara Air 5000 Liter Terhadap P-Delta - Anggrainy, Rita; Irawan, Teddy; Zulfiati, Ria (Universitas Muhammadiyah Palembang, 2025)
An unstable structure will undergo significantly greater deformation under loading compared to a stable structure. To enhance stability, one common method is the incorporation of a bracing system (structural reinforcement elements). Bracing helps resist vertical loads such as gravity, as well as horizontal or lateral forces such as earthquake loads, thereby reducing the potential for excessive vibration or sway in the building. The water tower, which functions as a storage structure, was analyzed using three bracing configuration models through structural analysis. The P-Delta effect in Model Type 1 reached 1.74 mm, while the minimum value was observed in Model Type 2 at 0.83 mm. In contrast, Model Type 3 showed a non-optimal P-Delta value of 1.52 mm. These variations occurred due to the influence of the different bracing arrangements. Model Type 2 demonstrated the most optimal P-Delta performance among the three configurations.